Charles Dickens : scenes from an extraordinary life - Manning, Mick (Frances Lincoln Childrens Books, 2011)
This picture book vividly dramatizes Dickens' life, beginning with his birth in Portsmouth and early childhood near the docks in Chatham, and follows the young Charles through the hardship of working in a blacking factory at the age of 10 to his years at school and his early career as a reporter. Key incidents that inspired the later novels are described, and his marriage, family life, dramatic readings and tours of the USA are included.